Allele distribution and phenotypic resistance to ciprofloxacin and gentamicin among extended-spectrum β-lactamase-producing Escherichia coli isolated from the urine, stool, animals, and environments of patients with presumptive urinary tract infection in Tanzania - Mwakyoma, Adam A.; Kidenya, Benson R.; Minja, Caroline A.; Mushi, Martha F.; Sandeman, Alison; Sabiti, Wilber; Holden, Mathew T. G.; Mshana, Stephen E. (Frontiers in Antibiotics, 2023)
Background Additional antimicrobial resistance to extended-spectrum β-lactamase (ESBL)-producing E. coli exhausts treatment options. We investigated allele distribution and resistance to ciprofloxacin and gentamicin among ESBL-producing E. coli isolates from the urine, stool, animals, and environments of presumptive urinary tract infection (UTI) patients, in order to gain a crucial insight toward devising prevention and control measures and treatment guidelines. Methods Archived ESBL-producing E. coli isolates from the urine, stool, animals, and surrounding environments of presumptive UTI patients were retrieved. Antimicrobial susceptibility profiles for ciprofloxacin and gentamicin were done followed by multiplex Polymerase chain reaction (PCR) for blaCTX-M, blaTEM, and blaSHV, to determine ESBL allele distribution. Data were analyzed using STATA version 17. Results A total of 472 confirmed ESBL-producing E. coli isolates from Mwanza 243 (51.5%), Kilimanjaro 143 (30.3%), and Mbeya 86 (18.2%) were analyzed. Of these, 75 (15.9%) were from urine, 199 (42.2%) from stool, 58 (12.3%) from rectal/cloaca swabs of animals, and 140 (29.7%) from surrounding environments. Out of the 472 ESBL-producing E. coli, 98.9% (467) had at least one ESBL allele. The most frequent allele was blaCTX-M, which was detected in 88.1% (416/472) of isolates, followed by the blaTEM allele, which was detected in 51.5% (243/472) of isolates. A total of 40.7% (192/472) of isolates harbored dual blaCTX-M + blaTEMalleles and only 0.2% (1/472) of isolates had dual blaCTX-M + blaSHValleles, whereas 2.3% (11/472) of isolates had a combination of all three alleles (blaCTX-M + blaTEM + blaSHV). None of the isolates harbored a combination of blaTEM + blaSHVonly. Resistance to ciprofloxacin and gentamicin was observed in 70.8% (334/472) and 46.0% (217/472) of isolates, respectively. There was a significant difference in the distribution of resistance to ciprofloxacin as well as gentamicin among ESBL-producing E. coli isolated from various sources (p-value < 0.001 and 0.002, respectively). Conclusion Almost all ESBL-producing E. coli isolates carry blaCTX-M, blaTEM, and blaSHV either alone or in combination, with the most common allele being blaCTX-M.The resistance to ciprofloxacin and gentamicin, which are frontline antibiotics for UTIs among ESBL-producing E. coli, is high. This implies the need to continually revise the local guidelines used for optimal empirical therapy for UTIs, and for continual research and surveillance using one health approach.